What’s So Hard about Improving Access to Water and Sanitation? - World Bank (World Bank, Washington, DC, 2016)
The World Bank is committed to ending extreme poverty and boosting shared prosperity. Providing clean, safe water to people wherever they live is critical to achieving these goals. A World Bank research team analyzed more than 130 water, sanitation and hygiene evaluations to understand what evidence there is for successful programs and what still needs to be learned. The researchers found that evidence is clear that improving sanitation and handwashing reduces diarrhea. The evidence is less clear when it comes to expanding services to large populations or changing behaviors, such as getting people to add chlorine to drinking water or to wash their hands. More research and more innovative programs are needed to establish the path forward.